The environmental impacts of land claim-discarded settlement development in Mamahule, Polokwane Local Municipality of Limpopo Province - Mathabatha, Lotty Elizabeth (My University, 2013)
Environmental impacts from a land claim-discarded settlement development are positive, negative and cumulative by nature, within the broad scope of environmental impacts there has been much focus on the physical environment neglecting the socio economic and other political factors of the environment. This study presents from a total environmental perspective the investigation of the environmental impacts of land claim-discarded settlement development in Mamahule ga-Matsaung. Both primary and secondary sources of data were used for the purposes of this study. The study used the non-probability purposive sampling for the entire targeted population. The study used both thick descriptions and qualitative techniques to analyse the collected data. Thick descriptions were used to explain the environmental impacts of various temporal phases as well as processes settlement development and land claim, while quantitative (Leopold matrix and Cost Benefit Analysis) were used to evaluate environmental impacts and economic valuations of the land claim and the settlement development. The study shows that the Environmental Impact Assessment should be conducted prior the development of any settlement to avoid multiple negative environmental impacts on the environment. The study also highlights the impact that land claim has on development activities and the way in which settlement development can delay the process of a land claim. The study arrived to a conclusions that both settlement development and land claim impacted differently on the environment.
Thesis ( M.Dev.) -- University of Limpopo, 2013
Keywords: Land claims; Land reforms; Environmental impacts; Land settlement -- South Africa; Pollution -- Environmental aspects